Optimizing conditions for microwave-assisted extraction of polyphenolic content and antioxidant activity of Barleria lupulina Lindl. - Ismail Suhaimy, Noor Wahida; Abd Gani, Siti Salwa; Zaidan, Uswatun Hasanah; Halmi, Mohd Izuan Effendi; Bawon, Paiman (MDPI, 2021)
Barleria lupulina Lindl. (Acanthaceae) as an ornamental plant has been widely used in folklore medicine due to its abundancy in polyphenolic compounds. The present study examined conditions for optimal extraction of antioxidants from B. lupulina leaf extracts by using the microwave-assisted extraction (MAE) method. The effects of ethanol concentrations, microwave power, and extraction time on total phenolic content (TPC), total flavonoid content (TFC), 1-diphenyl2-picrylhydrazyl (DPPH), and 2,20-azino-bis (3-ethylbenzothizoline-6-sulfonic acid) (ABTS) were investigated by single-factor experiments. Response surface methodology (RSM) was applied to observe interactions of three independent variables (ethanol concentrations, microwave power, and extraction time) on the dependent variables (TPC, TFC, DPPH, and ABTS) to establish optimal extraction conditions. Quadratic polynomial equations in all experimental models yielded favorably with fitted models with R2 and R2 adj of more than 0.90 and a non-significant lack of fit at p > 0.05. The optimal conditions for the extraction of antioxidant activity were established at 80% (v/v) ethanol, 400 W, and 30 s with TPC (238.71 mg gallic acid equivalent (GAE)/g sample), TFC (58.09 mg QE/g sample), DPPH (87.95%), and ABTS (89.56%). Analysis by ultra-high-performance liquid chromatography– quadrupole time-of-flight mass spectrometry (UHPLC-QTOF/MS) successfully identified four new phenylethanoid glycoside compounds in the species.